Peran dan Manfaat Media Sosial sebagai Sarana Pembelajaran di Era Society 5.0 - Renita Br. Saragih; Jelita Christy Sianipar; Neni Lasinta Lumban Siantar; Marfina Kristin Natalia Naibaho; Ferdin Harapan Jaya Gulo (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Society 5.0 pursues the concept of a human-centered society supported by digital technology. Social media has become an effective alternative for supporting student learning, but strict supervision is necessary to prevent rule violations. Besides aiding in learning, social media is also beneficial for various groups with its diverse features such as images and videos. Social media offers significant benefits in education, but its use must be wise to avoid negative impacts. In addition to assisting in learning, social media can also be used by different groups to share useful information.